Human Resources for Health in Major National Policies and Plans of Nepal - Mahato RK, Ghimire J, Gupta RP (Journal of Nepal Health Research Council, 2013)
Background: Nepal first began planning for human resources for health forty years back. Since then a number of long-term and short-term plans, policies and acts have been introduced. This study is conducted to analyse the HRH gap in relation to objectives, guidelines, and priorities of the Ministry of Health and Population. Methods: A combination of desk review of the HRH related policies, strategies, and plans of the government and stakeholder consultation was used for the study from October 2012 to March 2013. Ethical approval was obtained from the NHRC. Results: Almost all the plans and policies highlighted human resources as central to successful health systems in Nepal. Still there are several gaps at the implementation level. The expanding health programs with increasing demand for health services has demanded more robust evidence-based planning of HRH. There are many vacant positions due to complicated health act including the issue of social inclusions of workforce due to poor implementation of program policies. Conclusions: HRH needs to be recognized as dealing with more than just health personnel, but as assets necessary for the entire health system to function, plan, and manage it. There is the need to fill vacant positions in a timely manner, and increase the participation of excluded groups.